The impact of breastfeeding on lung development and function: a systematic review. (December 2013) - Waidyatillake, Nilakshi T; Allen, Katrina J; Lodge, Caroline J; Dharmage, Shyamali C; Abramson, Michael J; Simpson, Julie A; Lowe, Adrian J
With the global trend of increasing asthma and allergic disorders there is strong interest regarding early life nutrition as a potentially modifiable risk factor for lung disease. This systematic review includes 10 studies that assessed the effect of breastfeeding on lung growth and function. The review found breastfeeding to be beneficial for lung function, with the most consistent effect on increased forced vital capacity. There was no clear evidence that the relationship between breastfeeding and lung function was mediated through other factors. Furthermore, the findings from the few studies that investigated if maternal asthma modified the effect of breastfeeding on lung function were inconsistent. Further research is needed to determine the specific details such as duration and type (exclusive vs partial) of breastfeeding that leads to improved lung function.